EFEKTIFITAS LATIHAN KERJA DALAM HUBUNGANNYA DENGAN PEMANFAATAN TENAGA KERJA LULUSAN BALAI LATIHAN KERJA KABUPATEN SLEMAN DAERAH ISTIMEWA YOGYAKARTA - Mulyadi Mulyadi (LPPM UNY, 2000)
Abstract This research was aimed to investigate the relationship between training program implementation effectiveness, background of education and quality of skill to the use of labor viewed from the perspective of job compatibility to skill. The population was 1991-1993 graduates of the job Training House (BLK) majoring in motorcycle mechanics and carpentry numbering to 168 persons. The sample of study was drawn by a stratified proportional random sampling method, consisting of 114 persons. Data of background of education and skill quality were obtained by means of a documentation technique, while data on training program implementation effectiveness and labor force uses viewed from job compatibility to skill were derived by a questionnaire technique subjected to validity and reliability tests. The data were analyzed by a multiple regression technique and followed by a rank analysis. The result of study was concluded as followed: (1)63.13% of the BLK graduates worked incompatibly to their skill due to their skill qualification incompatible to job requirements; (2) the contribution of training effectiveness and background of education to quality of skill was 42.57%; (3) totally, the indirect contribution of training effectiveness, background of education, and quality of skill to the use of labor force viewed from the aspect of job compatibility to skill was 34.2% Keywords: labor force, job training house